2011
DOI: 10.1155/2011/854784
|View full text |Cite
|
Sign up to set email alerts
|

Multiple, Unilateral Lisch Nodules in the Absence of Other Manifestations of Neurofibromatosis Type 1

Abstract: Lisch nodules associated with Neurofibromatosis Type 1 (NF1) are usually multiple and bilateral in nature. Here, we report a 21-year-old healthy, Caucasian female who was diagnosed with multiple, unilateral Lisch nodules during routine eye examination. A thorough history and physical examination revealed no other signs of NF1. We diagnosed the rare occurrence of numerous, unilateral Lisch nodules in the absence of additional features of NF1 in our patient and provide a discussion concerning the differential di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…They are typically seen under slit-lamp examination; are described as round elevated nodules within the iris, measuring around 2-3 mm in size; and are brown to yellow in color (Figure 1). Lisch nodules are typically bilateral; however, unilateral nodules have been reported previously in some types of NF [4].…”
Section: Intraocular Manifestations 31 Irismentioning
confidence: 88%
“…They are typically seen under slit-lamp examination; are described as round elevated nodules within the iris, measuring around 2-3 mm in size; and are brown to yellow in color (Figure 1). Lisch nodules are typically bilateral; however, unilateral nodules have been reported previously in some types of NF [4].…”
Section: Intraocular Manifestations 31 Irismentioning
confidence: 88%
“…7 Multiple Lisch nodules are pathognomonic of NF1, as it is rare for Lisch nodules to occur in the absence of other features of NF1 8 ; however, several cases have been reported in the literature. 9,10 Lisch nodules must be carefully distinguished from other iritic findings, including iris mammillations, multiple iris nevi, iritic cysts, Brushfield spots, and malignancies. 8,11 Principally, the alternative diagnoses of iris mammillations and multiple iris nevi were considered in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…They can be clear to yellow or brown in color. 7,9,11 Multiple experienced pediatric ophthalmologists were consulted and agreed that the lesions in cases 1 and 2 appear most consistent with a combination of iris mammillations and Lisch nodules. As Legius syndrome was first described little over a decade ago, and our body of knowledge continues to expand, these cases may demonstrate that the full phenotypic spectrum of Legius syndrome has not yet been defined.…”
Section: Discussionmentioning
confidence: 99%
“…Ragge et al suggested that iris mammillations have been confused with Lisch nodules associated with NF1 which was previously known as von Recklinghausen disease [ 1 , 2 ]. Lisch nodules, also known as iris hamartoma, are irregularly spaced, pigmented brown hamartomatous nodular aggregates of dendritic melanocytes [ 1 , 6 ]. They are accompanied by ocular hypertension or intraocular malignancy, and they are also associated with external ocular manifestations such as oculodermal melanosis [ 1 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lisch nodules, also known as iris hamartoma, are irregularly spaced, pigmented brown hamartomatous nodular aggregates of dendritic melanocytes [ 1 , 6 ]. They are accompanied by ocular hypertension or intraocular malignancy, and they are also associated with external ocular manifestations such as oculodermal melanosis [ 1 , 6 ]. The iris nodules in our case were protruding nodules and had the same color as those seen in dark brown irides.…”
Section: Discussionmentioning
confidence: 99%